Evaluation of ancestry from human skeletal remains: a concise review - Cunha, E (2020)
Ancestry assessment represents a major component of forensic anthropological analysis of recovered human remains. Interpretations of ancestry, together with other aspects of the biological profile, can help narrow the search of missing persons and contribute to eventual positive identification. Such information can prove useful to authorities involved in the identification and investigative process since many lists of missing persons have a reference to this parameter. Recent research has strengthened available methodologies involving metric, non-metric morphological as well as chemical and genetic approaches. This review addresses the new anthropological techniques that are now available, as well as the complex historical context related to ancestry evaluation.